The VaccineLand: An Interactive Digital Board Game to Educate Public about Vaccines - Zulkifli, Zuhri Arafah; Mohd Noor, Mohamad Nornazmi; Mohd Johari, Nur Farahin (JOIV : International Journal on Informatics Visualization, 2022)
The invention of the COVID-19 vaccines has resulted in various viewpoints and reactions from the public. The vaccines are guaranteed to be safe and clinically proven to enhance human antibodies preventing the virus from spreading. However, disseminating facts and truth about vaccines to the public is challenging due to many factors, including vaccine hesitancy and skepticism. Besides, some individuals are still concerned about vaccines' adverse effects and safety. Plus, the presence of various misleading online discussions promoted by anti-vaccine activists that spread false information about vaccines has worsened the situation. Therefore, in this paper, we proposed a digital board game, the VaccineLand, that provides information about vaccines in terms of their history, reasons for taking them, and the adverse effects on the public. Thus, VaccineLand was established based on the Game-Based Learning (GBL) model by its goal, which is to provide the public with facts and knowledge about vaccines in an interactive way. GBL is known as a type of gameplay with specific learning outcomes. Interactive GBL corresponds to the use of educational game applications for learning. This study investigates a usability evaluation consisting of four variables (usefulness, ease of use, ease of learning, and satisfaction) involving a total of 40 respondents. The finding indicates that the usability of this game was highly acceptable. We believe that VaccineLand can be a helpful tool to educate the public about vaccines